Exploring The Association Between Learners' Academic Self-Concept and Academic Achievement In The English Subject - Maria Zefanya Tessera Soru; Yuni Utami Asih; Ida Wardani (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2023)
Academic achievement is significantly influenced by the cognitive and emotional involvement of students in their learning experiences, which are motivated by factors including academic self-concept. The purpose of this study is to elaborate the significant association of learners’ academic self-concept and academic achievement in the English subject. This research used quantitative data approach and analysis of Product-Moment according to Karl Pearson. There were two variables, namely academic self-concept (X), and Academic achievement (Y). There were 177 samples of this research out of 317 population gotten from simple random sampling. The value of the correlation between academic self-concept and academic achievement was 0.646 r-table (0.001) and the p-value was 0.001 lower than the significance level 0.05. Academic Self-Concept was in the high category because 68% out of samples got 67-82 and categorized as the high. More than 80% samples got scores 70-100 and the Academic Achievement categorized as the very high achievement. There was a significant positive correlation in a strong category between academic self-concept and academic achievement. It is because the higher and lower the score of Academic Self-Concept, the higher and lower the score of Academic Achievement and vice versa.